2015
DOI: 10.1260/1708-5284.12.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis of Eregli sugar factory

Abstract: Progressive decline in world energy resources, rising costs, on behalf of the various studies has led businesses to use energy resources efficiently. This work is at the top of the exergy analysis. In this study, using data from Eregli Sugar Factory 2010–2011 campaign year for sugar production processes, the first law of thermodynamics (energy analysis) and analysis of these condlaw (exergy analysis) were conducted. Depending on there sults of this analysis of the sugar production process yields the first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They concluded that by minimizing the energy loss and temperature change in heat transfer, the irreversibility of the process is reduced, and leads to an increase in the efficiency of sugar production (Bayrak et al, 2003). The lowest exergy efficiency after the steam production line was related to the evaporation line (Sahin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that by minimizing the energy loss and temperature change in heat transfer, the irreversibility of the process is reduced, and leads to an increase in the efficiency of sugar production (Bayrak et al, 2003). The lowest exergy efficiency after the steam production line was related to the evaporation line (Sahin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Şahin et al (2010) conducted research work on an old sugar plant in Turkey to renovate the plant and achieved similar results to those obtained by Bayrak et al Şahin et al investigated syrup production lines, clarification, evaporation, crystallization, and steam production as an open thermodynamic system and in steady state from the perspective of analyzing the first and second laws of thermodynamics. The lowest exergy efficiency after the steam production line was related to the evaporation line (Sahin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%